Walkway subgrade stabilization using fly ash - Leenaloshni, Joganathan (2014)
This thesis is about the walkway subgrade stabilization using fly ash. Fly ash has, been used as an additive which can improve the stabilization of subgrade. The objective of this thesis is to conduct testing in order to ascertain the engineering properties of soil and to determine the optimum moisture content of fly ash that give maximum CBR value for 5%, 10% and 15% soil-fly ash mixture. The effectiveness towards the soil by using different percentages of fly ash which is 5%, 10% and 15% was tested. For this research, a few laboratory tests were carried out to determine the improvement in the soil stabilization by using fly ash. From the result of the experiment, it can be concluded that the CBR value increases when the percentage of fly ash used in the soil mixture increases. This shows that the increases in amount of fly ash increases the compression and shearing strength of the soil and hence makes the subgrade to be more stabilized.